Physicochemical and Organoleptic Characteristics of Sourdough Bread with Kefir Grain Added to The Starter - Husni, Nayli; Novelina, Novelina; Hari, Purnama Dini (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Kefir grains function as a multifaceted starter comprising a variety of microbiota, such as lactic acid bacteria, yeast, and acetic acid bacteria, encapsulated within a polysaccharide matrix. This study investigates the efficacy of kefir grains in creating sourdough starters to assess sourdough bread's physical and chemical properties and identify the ideal formulation based on sensory acceptance. A Completely Randomized Design (CRD) comprised five treatments and three replications. Data were subjected to statistical analysis by Analysis of Variance (ANOVA) followed by Duncan's New Multiple Range Test (DNMRT) at a 5% significant threshold. The results indicated that including kefir grains in the sourdough starter markedly affected dough development, bread volume, acidity (pH), moisture content, ash content, protein content, carbohydrate content, and sensory characteristics, including texture and flavor. Treatment C, utilizing a 10% starting concentration, had the most advantageous outcomes, attaining enhanced sensory and compositional quality.